2018
DOI: 10.36076/ppj.2018.5.e545
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pulsed Radiofrequency with Continuous Radiofrequency Thermocoagulation at Low Temperature Improves Efficacy and Safety in V2/V3 Primary Trigeminal Neuralgia

Abstract: Background: Primary trigeminal neuralgia (TN) is a common clinical refractory neuralgia. Severe pain is experienced during episodes, severely impacting the patient’s quality of life. Long-term suffering from the disease can lead to anxiety, depression, and even suicide. The pathological processes involved in TN are complex, the mechanisms of pathogenesis are unknown, and effective treatment is lacking. Objective: This study aimed to assess the efficacy and safety of computed tomography (CT)- guided pulsed radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…At present, in the clinic, radio frequency current is used to treat neuralgia [ 14 ] and has been used extensively, such as in cases of paroxysmal collective headache [ 20 ], primary trigeminal neuralgia [ 15 , 21 - 23 ], glossopharyngeal neuralgia [ 24 ], PHN [ 11 , 12 , 25 , 26 ], chronic knee pain [ 27 ], and postherpetic trigeminal neuralgia [ 28 ]. In addition, certain studies on the use of different radio frequency modes for the treatment of neuralgia have been carried out consecutively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the clinic, radio frequency current is used to treat neuralgia [ 14 ] and has been used extensively, such as in cases of paroxysmal collective headache [ 20 ], primary trigeminal neuralgia [ 15 , 21 - 23 ], glossopharyngeal neuralgia [ 24 ], PHN [ 11 , 12 , 25 , 26 ], chronic knee pain [ 27 ], and postherpetic trigeminal neuralgia [ 28 ]. In addition, certain studies on the use of different radio frequency modes for the treatment of neuralgia have been carried out consecutively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain studies on the use of different radio frequency modes for the treatment of neuralgia have been carried out consecutively. Previous studies have shown that the effect of simple pulsed radiofrequency is not successful, whereas the therapeutic effect of pulsed radiofrequency combined with radiofrequency thermocoagulation is suitable for its clinical use [ 22 , 23 ]. In the comparative study of unipolar and bipolar groups, it has been found that the bipolar group exhibited more advantages in pain relief and functional recovery [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%